2018
DOI: 10.1103/physrevb.98.035437
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous charge distribution across gold nanoclusters measured by scattered low energy alkali ions

Abstract: The neutralization of low energy Na + and Li + ions scattered from Au nanoclusters formed by deposition onto oxide surfaces decreases as the cluster size increases. An explanation for this behavior is provided here, which is based on the notion that the atoms in the clusters are not uniformly charged, but that the edge atoms are positively charged while the center atoms are nearly neutral. This leads to upward pointing dipoles at the edge atoms that increase the neutralization probability of alkali ions scatte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 84 publications
(141 reference statements)
5
14
0
Order By: Relevance
“…A recent report from our group 22 agrees with work from the literature in that the clusters contain positively charged Au atoms, [55][56][57][58][59] although others have concluded that the clusters are overall negatively charged. [60][61][62][63] It was calculated from density functional theory (DFT) that the edge atoms of a nanocluster are the ones that are positively charged 59,64 and upward pointing dipoles are thus created at those sites.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A recent report from our group 22 agrees with work from the literature in that the clusters contain positively charged Au atoms, [55][56][57][58][59] although others have concluded that the clusters are overall negatively charged. [60][61][62][63] It was calculated from density functional theory (DFT) that the edge atoms of a nanocluster are the ones that are positively charged 59,64 and upward pointing dipoles are thus created at those sites.…”
Section: Discussionsupporting
confidence: 88%
“…50 As calculated in Table 1, between 7 and 10 Br atoms adsorb per nanocluster for 0.19 to 0.79 ML of deposited Au. Since the number of CO molecules is comparable to that of Br atoms per nanocluster, it is surmised that the Br atoms occupy the same edge sites as adsorbed CO. A drop off in the dipole strength of the nanocluster edge atoms occurs with 1.10 ML of Au due to inter-nanocluster effects that occur when the clusters are close to each other, as discussed previously, 22 thereby reducing their ability to dissociate Br2 and thus decreasing the amount of Br that adsorbs per cluster.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The appearance of the minor phase of In 2 O 3 and Au 2 O 3 which appeared in the XRD patterns before and after annealing may understood through the consideration of the bonding mechanisms. Since the bond length of InO (2.10 å) and that of AuO (2.08 å) are less than the bond length of MoO (2.24 å), The oxygen atom is subjected to stronger attraction force by the indium and Au. Thus, it prefer bonding with indium and Au rather than Mo.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of precursors and the subsequent catalytic reactions are generally considered to occur at the edges of the clusters [13][14][15][16][17]. In addition, density functional theory (DFT) has shown that the periphery atoms of Au clusters on oxide supports are positively charged while the center atoms are nearly neutral [13,14,18]. It has been proposed that oxygen in the substrate forms strong chemical bonds to the clusters that leads to charge transfer away from the edge atoms, and that this bonding is what produces the catalytically active sites on the nanoclusters [1,19].…”
Section: Introductionmentioning
confidence: 99%